Catalan Independence: Research and Personal Observations - Hersma, Kyle P. (My University, 2019)
A look into the current struggle for independence in the Spanish region of Catalonia requires, first, a more comprehensive understanding of nationalism, along with its history and evolution, before we can begin to put the Catalan independence movement into its proper perspective. After a brief discussion of nationalism, this paper seeks to describe the historical and cultural context surrounding Spain and Catalonia, enumerating some key examples that discuss important pillars in the Spanish national identity and crucial influencers on the cry for independence. Through the research of acclaimed Catalan scholars and my own perceptions in my brief time in the region, I hope to show examples of how my experiences both align with and dispute the prevailing outlook stated in the Catalan literature.